An account of some early libraries and book collections at the Cape of Good Hope, with special reference to the establishment of the South African Public Library - Tyrrell-Glynn, William Henry Patrick Aloysius (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 1972.